THE POWER OF PANCASILA VALUES IN BUILDING THE PERSONALITY OF THE INDONESIAN COMMUNITY: NILAI NILAI PANCASILA - FIRMASARI, CINDY AULIA (PRODI PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN STKIP PGRI SUMENEP, 2025)
Pancasila as the basis of the state and the way of life of the Indonesian people has a very important role in building the personality of society. The values contained in Pancasila, namely Belief in One Almighty God, Just and Civilized Humanity, Indonesian Unity, Democracy Led by Wisdom in Deliberation/Representation, as well as Social Justice for All Indonesian People, are the moral and ethical foundations in social interactions. This research aims to analyze the power of Pancasila values in shaping the character and identity of diverse Indonesian society. The method used is literature review and qualitative analysis of the implementation of Pancasila values in everyday life. The research results show that the application of Pancasila values can strengthen a sense of unity, increase tolerance between groups, and encourage active community participation in the democratic process. Apart from that, Pancasila also functions as a tool to overcome conflict and differences, thereby creating a harmonious and just society. Thus, strengthening Pancasila values in education and social life is very necessary to build the personality of the Indonesian people who are strong and have integrity.